Probing the impact of obesity and overgrowth on heart function using a Drosophila model - Andrews, Rachel M (My University, 2023)
The cardiac extracellular matrix (ECM) is a dynamic protein scaffold that is required to support cardiac function. Regular remodelling of the matrix involves protein turnover and deposition and is a highly regulated process. In disease states the normal balance of the ECM is disrupted and aberrant protein deposition and crosslinking can occur. This process, termed fibrosis, causes stiffening of the cardiac ECM, which in turn impairs organ function. Fibrosis is a hallmark of cardiovascular disease, is a progressive condition that can contribute to adverse clinical outcomes, and currently has no available treatments. One of the leading causes of cardiovascular disease is obesity and fibrosis is known to occur in this context. In order to investigate the development of fibrotic remodelling in the context of obesity I have developed a dietary obesity model in the fruit fly Drosophila melanogaster. Additionally, I developed a genetic overgrowth model as increased cardiac load is also known to trigger fibrotic remodelling. Dietary obesity models reveal altered ECM organization, as well as impaired cardiac contractility, while overgrowth models demonstrate a remarkable ability to appropriately scale heart morphology with increased body size. The overgrowth model does have extremely elevated expression levels of the crosslinking enzyme LOXL2, suggesting a major contributor to impaired function is increased crosslinking rather than altered protein deposition. However, inhibition of crosslinking caused only minor ECM organizational defects but was able to rescue the elasticity of the overgrowth model. Overall, this thesis raises intriguing questions for treatment of cardiovascular disease, where tissue dynamics are often overlooked in a clinical setting.
Keywords: Drosophila, obesity, heart disease, overgrowth, extracellular matrix, crosslinking